Alteração do estresse oxidativo da periodontite como fator de risco para o desenvolvimento da pneumonia associada à ventilação mecânica: estudo clínico, observacional do tipo transversal - Silva, Bruna Belineli Gomes Frisso (2023)
Enzyme-laden saliva associated with periodontal disease can modify mucosal surfaces to promote adhesion and colonization by respiratory pathogens. The objective of this study was to evaluate the occurrence of oxidative stress resulting from periodontal inflammation in the development of VAP in patients admitted to the Intensive Care Unit (ICU). Methodology: Clinical, cross-sectional and observational study, with quantitative analysis of data, with clinical and laboratory basis. Collections were carried out from April 2022 to January 2023. The selected patients were evaluated for the presence or absence of periodontitis and VAP. 117 patients were evaluated, and after applying the inclusion and exclusion criteria, 53 patients were included in the study and were divided into 3 groups: 1- Control – without periodontitis and without VAP (n=17), 2- Periodontitis and without VAP (n=30), 3- Periodontitis and with VAP (n=6). A periodontal clinical examination was carried out: Clinical Probing Depth (PCS), Bleeding on Probing (SS) and Clinical Insertion Depth (PCI), in addition to collecting and quantifying gingival crevicular fluid, collecting saliva and tracheal secretion for system analysis antioxidant and oxidative stress. Hematological exams and patient data were collected from electronic medical records (Tasy®) and data for diagnosing VAP were provided by the Hospital Infection Control Committee. The variables referring to clinical evaluations and biochemical analyzes were evaluated for normality (Shapiro-Wilk test) and homoscedasticity (Bartlett test) and then analyzes were carried out between groups using the Kruskall Wallis non-parametric test., followed by the Dunn test. Results: The average age of the patients was 49.8 years, with the majority being male. The clinical variables of PCS, PCI and SS, in the group of patients with periodontitis but without VAP, presented significantly higher values than the control group. Regarding hematological tests, urea and creatinine showed statistically significant differences. When evaluating variables related to the antioxidant system and oxidative stress in saliva, the SOD enzyme was inhibited and LPO was increased in the periodontitis group when compared to the control group. There was an increase in SOD, CAT and GR and a decrease in LPO in the Periodontitis+Pav group in relation to the Periodontitis group. The integrative analysis showed a greater contribution of the CAT and GST enzymes with positive scores in the Periodontitis+VAP group. Analysis of the same variables, but in tracheal secretion, showed that GST and LPO presented a decrease in the group of patients with periodontitis compared to the control group. The GR and GST enzymes showed induction and inhibition, respectively, in the Periodontitis + VAP group and the same results were observed in the integrative analysis of tracheal secretion. Conclusion: the change in oxidative stress caused by the inflammation of periodontitis with an imbalance in the antioxidant status may be a risk factor for the development of VAP. Clinical studies with larger samples and longer collection times are needed to confirm these findings.